2015
DOI: 10.3892/mmr.2015.3581
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents osteoporosis in ovariectomized rats by regulating microRNA-338-3p

Abstract: Osteoporosis is a disease characterized by loss of bone mass and degeneration of the microstructure of bone. Resveratrol (3,5,4-tri-hydroxystilbene; RESV) may delay the onset of a variety of age-related diseases. In the present study, an ovariectomized female rat model was used to detect the changes in microRNAs (miRNAs/miRs) following RESV treatment. Subsequently, the target genes of miRNA were predicted using TargetScan software and determined using a dual-luciferase reporter assay. Finally, the role of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 19 publications
0
53
0
Order By: Relevance
“…Liu et al demonstrated that miR-338-3P suppressed the expression level of osterix, a transcription factor for osteoblast differentiation in BMSCs by targeting Runx2 and Fgfr2 [ 89 ]. Moreover, resveratrol could prevent the bone loss in ovariectomized rats by inhibiting miR-388-3P [ 90 ]. MiR-125b shows a negative effect on osteogenesis by targeting osterix.…”
Section: Regulatory Roles Of Micrornas In Bone Remodelingmentioning
confidence: 99%
“…Liu et al demonstrated that miR-338-3P suppressed the expression level of osterix, a transcription factor for osteoblast differentiation in BMSCs by targeting Runx2 and Fgfr2 [ 89 ]. Moreover, resveratrol could prevent the bone loss in ovariectomized rats by inhibiting miR-388-3P [ 90 ]. MiR-125b shows a negative effect on osteogenesis by targeting osterix.…”
Section: Regulatory Roles Of Micrornas In Bone Remodelingmentioning
confidence: 99%
“…In a recent study, resveratrol, which is a polyphenolic phytoestrogen with osteogenic and osteoinductive properties, exhibited the ability to prevent osteoporosis by suppressing miR-338-3p. Mechanistically, resveratrol treatment leads to suppressed miR-338-3p, followed by an increase in Runx2 expression [ 97 ].…”
Section: Epigenetic and Osteoporosismentioning
confidence: 99%
“…Presently, more than a hundred papers have confirmed that the effect of RSV in the prevention or treatment of various diseases, including prostate cancer [ 15 ], melanoma [ 16 ], breast cancer [ 17 ], lung tumors [ 18 ], white adipogenesis [ 19 ], liver steatosis [ 20 ], inflammation [ 21 , 22 ], neurodegenerative disorders [ 23 ], and osteoporosis [ 24 ], were mediated by miRNAs.…”
Section: Introductionmentioning
confidence: 99%